HPV vaccination intent and willingness to pay for 2-, 4-, and 9-valent HPV vaccines: A study of adult women aged 27–45 years in China. Issue 14 (23rd March 2020) - Lin, Yulan; Lin, Zheng; He, Fei; Chen, Huilin; Lin, Xi; Zimet, Gregory D.; Alias, Haridah; He, Shuqiong; Hu, Zhijian; Wong, Li Ping
Abstract: Objective: This study aims to investigate acceptance and willingness to pay for HPV vaccination among adult women in China. Methods: An online survey was sent to mothers aged 27–45 years of primary school pupils in the Fujian province, China. Participants completed questions about HPV related knowledge and health beliefs, intention to take the HPV vaccine and the willingness to pay for bivalent vaccine (2vHPV), quadrivalent vaccine (4vHPV), and 9-valent HPV vaccine (9vHPV). Results: Of a total of 2339 complete responses, 58.3% reported intent to obtain HPV vaccine. Mothers who were younger in age, residing in urban, working in managerial or professional occupations, who knew someone with cervical cancer and who were able to make independent decisions about the HPV vaccine ( vs . joint decision with spouse) were more likely to express intent to have HPV vaccination. Perceived barriers, cues to action and self-efficacy were three of the constructs in the health belief model that significantly influenced HPV vaccination intent. A higher proportion of participants expressed willingness to pay for 2vHPV (81.2%) and 4vHPV (75.9%), as compared to 9vHPV (67.7%). Conclusion: Adults women expressed moderate intention to receive the HPV vaccine. Intervention to address barriers to uptake of the HPV vaccine among adult women in China is warranted.